Botanical art techniques : a comprehensive guide to watercolor, graphite, colored pencil, vellum, pen and ink, egg tempera, oils, printmaking, and more - Woodin, Carol; Jess, Robin A.; Timber Press (Portland, Or.); American Society of Botanical Artists (Portland, Oregon : Timber Press, 2020)
The ultimate how-to guide to the essential botanical art techniques from the people who know it best, the American Society of Botanical Artists. Helpful tutorials covers watercolor, graphite, colored pencil, vellum, egg tempera, oils, pen and ink, and printmaking.-- adapted from back cover.
Getting started. Caring for cut flowers Wild plants in the field Working in a backcountry location Setting up a studio Basic botany for botanical artists - Part 1. Drawing botanical subject in black and white. Graphite skills. Applied tutorials : Shaded flowers Leaves Fruits, vegetables, and branches Drawing spiral and diagonal patterns - Advanced tutorials : Drawing an inflorescence with many flowers in graphite Illustrating a plant portrait from roots to tips - Pen and ink. Applied tutorial : Drawing a thistle head in seed - Advanced tutorials : Depicting cactus spines Making a scientific ink dissection drawing with technical pens Scientific botanical illustrations in pen, brush, and ink - Part 2. Botanical subjects in color, Colored pencils. Applied tutorials : Three flower types in colored pencil Depicting leaf texture with colored pencil Fruit and vegetables in colored pencil - Advanced tutorials : Grisaille techniques on rose hips with colored pencil and watercolor pencils Kiwi vine n colored pencil and graphite A crabapple branch in colored pencil on film - Watercolor on paper - Properties of watercolor paints - Palette philosophies - Transferring a drawing onto paper or vellum before painting begins - Watercolor wash and wet techniques - Applied tutorials : Drybrush layering, glazing, and detailing Flowers Leaves Stems, twigs, and roots Painting a leaf in sepiatone - Advanced tutorials : Painting a slipper orchid using wet techniques and masking fluid Painting gloss, bloom, and reflected light in grapes Drybrush watercolor and color mixing Creating an in-situ painting Painting a magnolia with watercolor washes Drybrush tomato with masking fluid - Watercolor on vellum. Applied tutorials : Drybrush lines, washes, and crosshatching on Kelmscott vellum Painting a dried leaf on vellum Painting bloom on fruit - Advanced tutorials : Achieving deep, rich color in watercolor in Kelmscott vellum Using opaque watercolors on dark vellum Painting a flowering cherry tree bough - Specialized techniques and composition. Field sketchbook and journal Egg tempera, gouache, and casein: a comparison Etching techniques Painting a branch with lichens in gouache and watercolor Gouache on paper: spruce needles and cones Metalpoint Painting in acrylics Painting on Oils - Composition. Composition in practice Elements and principles of composition in botanical art Different approaches to botanical composition.
Includes bibliographical references (page 398) and index.
Keywords: Botanical illustration -- Technique; Plants in arts catalogs; Flowers in art